PENGKLASIFIKASIAN CALON KANDIDAT CUSTOMER SERVICE TERBAIK DENGAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Juna Eska; Afni Nia Sari; Hidayatullah Hidayatullah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2023)
PT. Telkomsel is one of the companies engaged in the telecommunications sector, for supervisors it is very difficult to determine each customer service candidate who is the best, resulting in jealousy between other candidates. PT. Telkomsel needs to determine a strategy to make it easier to process data for each input value, namely by Simple Additive Weighting (SAW). This method is one of the most frequently applied methods to find out the best values a company needs to maintain smoothness in selecting the best candidates. From the research it can be concluded that each variable can be determined by dividing the most prioritized value, namely 0.5 Skill Variables, 03 Knowledge Parameters, 02 Attitude Parameters and with customer service data of 25 employees.